Neuroprotective Effect of Withania Somnifera Root Extract In Type 2 Diabetes Mellitus Induced Cognitive Impairment And Neurodegeneration In Rats - Tanwar, Anshul; Gulati, Kavita; Ray, Arunabha (Asian Journal of Pharmaceutical Research and Development, 2022)
The present study was conducted to assess the effects of Withania somnifera root extract (WS) on cognitive deficit and neurodegeneration induced by type 2 diabetes mellitus in rats. Type 2 diabetes mellitus (T2DM) was induced in rats by feeding them high fat diet (HFD) for 8 weeks followed by intraperitoneal administration of low dose Streptozotocin (STZ; 35 mg/kg). After four weeks of STZ administration the levels of metabolic parameters (fasting blood glucose, serum triglycerides and serum total cholesterol) were measured to confirm the development of diabetes. WS and Pioglitazone (PZ) were administered daily for 8 weeks to the diabetic rats. At the end of the treatment, behavioural analysis was done to observe the effects of diabetes on memory by Morris water maze (MWM) test. Thereafter, animals were sacrificed; blood and brain samples were collected for biochemical analysis. Metabolic parameters (fasting blood glucose, serum triglycerides and total cholesterol) were found to be significantly elevated in diabetic rats as compared to normal control animals; treatment with WS and PZ for 8 weeks significantly lowered these levels. In MWM test, mean escape latency time (ELT) on day 4 was found to be increased and time spent in the target quadrant (TSTQ) on day 5 was reduced significantly in DC rats as compared to NC. However, TSTQ increased significantly and mean ELT was found to be decreased in the rats treated with WS at the dose of 100 and 300 mg/kg for 8 weeks as compared to DC rats. The level of Aβ1-42, a main component of amyloid plaques, was found to be increased significantly in hippocampus and prefrontal cortex of DC rats as compared to NC and treatment with WS lowered the levels of Aβ1-42. Further, the level of brain-derived neurotrophic factor (BDNF) was found to be reduced significantly in diabetic rats whereas WS treated groups showed a significant increase in BDNF. The data suggests that treatment with standardized root extract of Withania somnifera normalized the elevated metabolic parameters in diabetic animals when compared with untreated diabetic animals and the results were comparable with pioglitazone. Also it was found that T2DM adversely affects memory and cause neurodegeneration. WS treatment showed neuroprotective effects and improved memory retention in diabetic animals. Thus root extract of Withania Somnifera may have neuroprotective effects for the management of T2DM induced cognitive deficit.